Thermospheric density enhancement and limb O 130.4 nm radiance increase during geomagnetic storms. (March 2022) - Zhang, Yongliang; Paxton, Larry J.; Schaefer, R.
Abstract: We explore a connection between thermospheric density enhancement and increase in thermospheric O 130.4 nm radiance. We observe TIMED/GUVI enhancements in the limb 130.4 nm radiances at ∼400 and ∼520 km on the dayside during four intense geomagnetic storms in 2003 and 2004. The enhancements were well correlated with Dst and CHAMP total neutral density at 400 km which represents O density as O is the dominant species at those altitudes. At the 400 and 520 km altitudes, O 130.4 nm emissions are mostly created by two comparable sources: solar resonance scatter and photoelectron impact excitation. The coincident disk 130.4 nm radiances, mostly due to emissions below 200 km (peaked around 130–140 km), were not clearly correlated with the limb radiances. Because the limb 130.4 nm radiances depend on O density, solar EUV and 130.4 nm fluxes, variations in the limb 130.4 nm radiance respond mostly to changes in O density when the solar EUV and 130.4 nm fluxes are stable. This explains the good correlation (correlation coefficients up to 0.98) between the limb 130.4 nm radiance and CHAMP neutral density. Once a quantitative relationship is established between GUVI limb 130.4 nm radiance and neutral density under both quiet and disturbed conditions and at different altitude levels through empirical or radiative transfer modeling, the limb 130.4 nm radiances can be used to retrieve O density profiles in the upper thermosphere. Highlights: GUVI limb 130.4 nm radiances at ∼400 and −520 km were significantly enhanced during geomagnetic storms. The 130.4 nm radiance enhancements were strongly correlated with CHAMP neutral density at 400 km and Dst index. The enhanced 130.4 nm radiances are the signature of the storm-time increase in upper thermosphere O density.